The legal recognition of indigenous interests in Japan and Taiwan - Gao, Xiangpeng; Charlton, G.; Takahashi, M. (LexisNexis Hong Kong, 2016)
© 2016 School of Law, City University of Hong Kong.This article examines the legal recognition of indigenous interests in Japan andTaiwan. Both these states havemoved largely away from an ethnically defined conception of national identity and have taken steps to legally recognise and protect indigenous communities and autonomy. However, the process has privileged indigenous cultural policies while providing less protection for other rights such as autonomy and control of natural resources. This article argues the emphasis on cultural protection and the rhetorical embrace of other indigenous rights without the concomitant policy and legal implementation is because international indigenous norms remain prescriptively ambiguous in the Japanese and Taiwanese context and are difficult to reconcile with Japanese and Taiwanese national identities.